(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The objective of the present investigation was to study the antidiabetic and diuretic potential of Anogeissus latifolia (A. latifolia) bark in experimental rats. The A. latifolia bark was extracted with hydro-alcoholic solvent by cold extraction method. Acute toxicity study was performed according to OECD 425 guidelines for hydro-alcoholic extracts of A. latifolia bark (ALBE). The dose of 150 mg/kg p.o. and 300 mg/kg, p.o. of ALBE was selected for further studies. Animals were prepared diabetic by administration of alloxan (120 mg/kg, i.p.). The albino rats were divided in to five groups for oral glucose tolerance test (OGTT) and alloxan induced anti diabetic model with six animals in each group. Diabetic animals were treated with hydro-alcoholic extract of A. latifolia bark for 20 days. The blood glucose level was estimated according to standard procedures. Diuretic activity hydro-alcoholic extracts of A. latifolia was evaluated by Lipshitz method. The result shows that hydro-alcoholic extract from bark of Anogeissus latifolia 300 mg/kg (ALBE-II) shown significant hypoglycemic activity as compared to glibenclamide and diabetic group. The ALBE does not exhibit significant diuretic activity which is considered as positive marker in diabetic phenomena. Hence in present study extract of A. latifolia posses antidiabetic activity. This study may be benchmark in future to use of this drug scientifically.